Stosunki ukraińsko-polskie w XVII wieku: rola świadomości narodowej i konfliktu narodowościowego w powstaniu Chmielnickiego - Sysyn, Frank E. (1982)
p. 67-92
Summary in English.
Keywords: Cossacks - Ukraine - 17th c.; national consciousness - Ukraine - 17th c.; Cossack-Polish War, 1648-1657; Ukrainian-Polish relations 17th c.; Ukraine 17th c. - ethnic relations

Between the Ideal and Reality: Polish Woman in the 16th-18th Centuries - Bogucka, Maria (1929–2020) (Wydawnictwo Naukowe Semper, 2001)
p. 67-78
Keywords: Poland 16th c., 17th c., 18th c.; women; social history; gender studies; women - Poland - social conditions - 1500-1800

Karta tytułowa staropolskiej książki drukowanej - Juda, Maria (Wydawnictwo Naukowe "Semper", 2002)
p. 67-78
Summary in English.
Keywords: printing - Poland - 1500-1800; typography - Poland 1500-1800

Proklamowanie Białoruskiej Socjalistycznej Republiki Radzieckiej - Pyzel, Piotr (Wydawnictwo Naukowe Semper, 2007)
Summary in English and Russian.
p. 67-93
Keywords: Belarus - politics and government 1900-1945; Soviet Union - Politics and government - 1917-1953

Płace realne w 1939 i w 1944 roku : (próba porównania) - Imbs-Jędruszczak, Hanna (1929–2002) (Państwowe Wydawnictwo Naukowe, 1965)
p. 67-81 : ill.
Author's name: Hanna Jędruszczak.
Keywords: wages - Poland - 1900-1945

Idea wojska polskiego w Rosji po obaleniu caratu i walka o jej realizację - Wrzosek, Mieczysław (1930–2015) (Państwowe Wydawnictwo Naukowe, 1967)
p. 67-85
Keywords: Poles - Russia - 1900-1945; Poles - Soviet Union - 1900-1945; Poland - armed forces - Russia - 1900-1945; Soviet Union - 1917-1921 (Revolution) - Polish participation

Polska lokalna - Mierzwa, Janusz (1978– ) (Instytut Historii PAN, 2019)
Wydanie I.
p. 67-79 ; 24 cm
Keywords: Poland - 1918-1939 (Second Polish Republic) - historiography; Poland - politics and government - 1918-1939; local administration - Poland - history; local government - Poland - history - 20th c.

Pogrom warszawski 1881 r. - Markowski, Artur (Instytut Historii PAN, 2019)
p. 67-85
Wydanie I.
Keywords: Jews - Poland - 19th c.; Jews - Poland - 1900-1945; Antisemitism - Poland - 19th c.; antisemitism - Poland - 1900-1945; Jews - persecutions - Poland - 19th c.; Jews - persecutions - Poland - 1900-1945

Odpowiedź na ankietę - Kisielewski, Tadeusz (1939–2012) (Instytut Historii PAN, 2008)
p. 67-77
Keywords: Poland - 1944-1989 (Polish People's Republic) - historiography

Emeryci w przestrzeni społecznej Polski gomułkowskiej - Jarosz, Dariusz (1959– ) (Instytut Historii PAN, 2013)
The purpose of the article is an analysis of conditions and social situation of retired persons in the Polish People’s Republic in 1956–1970. It was based mainly on materials stored in the Central Archives of Modern Records, Archives of Polish Radio and Television and the results of sociological and statistical research. Certain contributions to the subject could be found in the specialist, informational and socio-cultural press.In the light of research evidence, the place of retirees within social space of Gomułka’s Poland was conditioned by several factors. The most important were:1. Demographic and social factors (composition and size of the group of people of retirement age, a scale of migration from the country to town and cities).2. Social policy, including mainly the solutions of the retirement and pension system (scale of the availability of retirement pensions, their amount depending on the period they were granted, i.e. the old and new pension portfolio).3. Low standard of retirement pensions which determined extremely harsh living conditions of retired persons and pensioners. Despite pension rises in 1956 and 1958, as late as in 1966 circa 70 percent of pensions were below the official minimum subsistence level for that year. On the opposite pole there were privileged groups with pensions twice as high; those included retired miners, military men, functionaries of the Ministry of Internal Affairs and prison officers, as well as the so-called people with special merits. Old people (including retired persons) were living in accommodations poorly equipped with basic systems of technical infrastructure. Their health deteriorated with advancing age; in the mid-1960s circa ten percent either did not leave house or was bedridden.4. The continuation (or not) of their professional work, which was significantly hampered by the system solutions passed in 1958 and 1968.All these factors had an impact on the retirees’ awareness, attitudes and behaviours. The world of their social contacts was gradually shrinking into the family circle. At the same time the status of retired person was accompanied more and more often not only by infirmity, but also by acute feelings of loneliness and isolation. The then system of social welfare and security was unable to meet these needs.
p. 67-92
Tables included.
Eng. summary
Keywords: retired people - Poland - social situation; old age - sociology; Poland - social policy - 1945-1970; social insurance - Poland - 1945-1970

Ukraińskie uniwersum symboliczne w Drugiej Rzeczypospolitej: inwazja integralnego nacjonalizmu - Zajcev, Oleksandr (Instytut Historii PAN, 2012)
p. 67-84 ; 24 cm
Keywords: social history - 1900-1945; Poland - social conditions - 1918-1945; Poland - 1918-1939 (Second Polish Republic); Ukrainians - Poland - 1900-1945; Ukrainians - Poland - identity - 1900-1945; nationalism - Ukraine - 1900-1945; symbolism in politics - Poland - 20th c.

Uwiedzeni, zmanipulowani, zdesperowani? Młodzież komunistyczna w Drugiej Rzeczypospolitej - Zieliński, Konrad (1971– ) (Instytut Historii PAN, 2013)
p. 67-92 ; 24 cm
Keywords: socialization - Poland - 1900-1945; Poland - social conditions - 1918-1939 (Second Polish Republic); communism and youth - Poland - 1900-1945; Komunistyczna Partia Polski and youth - Poland; youth - political activity - Poland - 1900-1945; youth - Poland - attitudes - 1900-1945

Szkoły i studia na włoskim szlaku 2 Korpusu Polskiego - Draus, Jan (1952– ) (Instytut Historii PAN, 2021)
The present publication outlines the problems related to the educational activity of the 2nd Polish Corps in Italy. The divisions of the 2nd Corps provided general and vocational education, as well as studies at Italian universities. General Władysław Anders’ 2nd Corps not only won glory on the battlefields, e.g. by taking Monte Cassino or liberating many Italian cities, but also, through its educational activities, prepared soldiers for civilian life at home and abroad.
p. 67-90
Summary in English
Keywords: 2nd Polish Corps; Italy; education; studies; Anders, Władysław (1892-1970); Poland. Polskie Siły Zbrojne. 2. Korpus; soldiers - education, non-military - Poland - history - 1900-1945; soldiers - education - Poland - history - 1900-1945; Polish soldiers - abroad - intellectual life - 20th c.; Polish soldiers - Italy - education - history - 20th century; schools, Polish - abroad - 1900-1945

Wychowanie patriotyczne w działalności oświatowej polskiej emigracji niepodległościowej na przykładzie Wielkiej Brytanii w latach 1945–1990 - Jastrzębska-Golonka, Danuta (2019)
The article is devoted to the emigrant educational activity among Polish refugees in Great Britain after 1945. For Poles living outside the country patriotic education was one of the most important educational tasks shaping their national identity. The teaching of patriotism was based on the sharing of knowledge about Poland, its history and culture, especially through symbolic references to Polish tradition, including national holidays: 3 May and 11 November – not recognized by the socialist government in the country but celebrated abroad to preserve historical memory and national identity as well to struggle for Independent Poland.
p. 67-89 ; Summary in Polish and English
23 cm
Keywords: Poland - emigration and immigration - 1945-1990; Polish people - education - abroad - 1945-1990; Polish schools - Great Britain- 1945-1990; National holidays - Poland; national holidays celebration - Poland; independence; patriotic education

Stanowisko mocarstw anglosaskich wobec powstania państwa polskiego w 1918 roku - Nowak-Kiełbikowa, Maria (1930–2013); Spustek, Irena ( –2013) (Państwowe Wydawnictwo Naukowe, 1979)
Summary in English.
p. 67-87
Keywords: Polish question, 1914-1918; World War I (1914-1918) - diplomatic history

"Hic liber libenter legitur in Polonia" : mapping the popularity of the "Zodiacus vitae in Poland" between the sixteenth and seventeenth centuries - Lepri, Valentina (Wydawnictwo Naukowe "Semper", 2015)
Marcellus Palingenius Stellatus’ Zodiacus vitae was one of the biggest editorial sensations of the sixteenth century, despite which its popularity in the Renaissance has not yet been the subject of a comprehensive study. The aim of this article is to partially fill that gap by addressing the circulation of the work in sixteenth-century Poland, where the first adaptation of the text into a language other than Latin was produced by the poet Mikołaj Rej. Indeed, several other illustrious exponents of Polish Renaissance culture were alsointerested in the Zodiacus and we can find references to it in both poetic works and in philosophical treatises. The particular political and social organisation of Poland at the time, and its intensive contacts with Italian and German universities, make it an excellent field of investigation for an understanding of the impact of the Zodiacus between the end of the sixteenth century and the beginning of the seventeenth.
Summary in English.
p. 67-93
Keywords: Manzolli, Pietro Angelo (ca 1500-1543), Zodiacus vital; Renaissance literature - history and criticism; Renaissance literature - Polish translations; neoplatonism; humanism; Renaissance - Italy

Dwie wojny światowe: opór, guerilla, résistance - Duraczyński, Eugeniusz (1931–2020); Molenda, Jan (1930– ) (Wydawnictwo Kronika Marian B. Michalik, 1996)
p. 67-77
Keywords: World War, 1914-1918; World War, 1939-1945 - underground movements

Commemoration of the 1905 Revolution in the Industrial City : The Case of Łódź - Śmiechowski, Kamil (1985– ) (Instytut Historii Polskiej Akademii Nauk, 2022)
The article discusses the current practices of commemorating the 1905 revolution in Łódź. The changes taking place in the city’s memory policy are conditioned both by the loss of memory of the events from a century ago and by changing political factors in the post-transformation period. The city is a paradigmatic example of a post-industrial city in Central and Eastern Europe facing an identity crisis. Narratives formulated ‘from above’ compete with those created ‘from below’. While the former are based on the construction of a utopian, capitalist city of success, the latter claim the history of the people of Łódź. Revitalising the memory of the Revolution of 1905 plays a key role in these negotiations, contributing to a revision of the post-transformation amnesia about the city’s working-class past
p. 67-87
Keywords: collective memory; politics of memory; urban memory; Revolution of 1905; history of Łódź; urban social movements

The Internal Situation in the Polish-Lithuanian Commonwealth (1769-1771) and the Origins of the First Partition (In the Light of Russian Sources) - Dukwicz, Dorota (Wydawnictwo Naukowe "Semper", 2011)
p. 67-84
Keywords: Poland 18th c.; Poland - politics and government - 1763-1796; Russia - foreign relations - Poland - 18th century; Poland - foreign relations - Russia - 18th century; Poland - 1772 (First Partition); first partition of Poland (1772)

Kartki na wojnę, której nie było : planowany mechanizm reglamentacji artykułów pierwszego zapotrzebowania w PRL w wypadku sytuacji nadzwyczajnej - Zawistowski, Andrzej (1973– ) (Wydawnictwo DiG, 2016)
Twentieth–century Poland experienced four periods of rationing basics: 1915–1921 (i.e. the First World War and the Polish–Bolshevik war), 1939–1949 (World War II and the post–war period), 1951–1953 (the height of Stalinism), and 1976–1989 (the breakdown of the communist economy and years of a universal lack of commodities in shops). Against this background the fact that during the 1961 Berlin Crisis the authorities of the People’s Republic of Poland made preparations for rationing in case of an extraordinary situation remains totally unknown. The system in question was based upon the structures of the Civic Militia, but was never applied, even when conditions prevailing on the domestic market required rapid intervention and the introduction of rationing (e.g. in 1976). The article presents the system in question as well as its structure, organisation, and evolution. The author tried to solve the question why this carefully planned system and millions of printed ration cards were destroyed and never used.
p. 67-81
Summary in English.
Keywords: Poland - economic conditions - 1944-1989; ration cards; socialism - economic aspects; shortage economy; crisis management; trade regulation - Poland - 1945-1990

Polityczne aspekty funkcjonowania Instytutu Badawczego Europy Wschodniej i Szkoły Nauk Politycznych w Wilnie (1930–1939) - Libera, Paweł (1979– ) (Instytut Historii PAN, 2021)
The Scientific and Research Institute of Eastern Europe and its affiliated School of Political Sciences were established in early 1930 in Vilnius. Closely associated with the academic community of the Stefan Batory University, they became a permanent part of the intellectual history of the city, primarily through their research and staff of eminent experts on the Soviet Union.
p. 67-84
Summaries in English
Keywords: Scientific and Research Institute of Eastern Europe in Vilnius; Sovietology; politics of nationality

The Polish Catholic Church and the Public Memory of the Shoah: Between Mnemonic Backlash and Settling Accounts with the Past - Nowicka-Fraanczak, Magdalena (Instytut Historii Polskiej Akademii Nauk, 2023)
The paper discusses the Polish Catholic Church’s ambiguous contribution to the public debate on settling accounts with the Polish-Jewish wartime past. The Church is an actor of right-wing historical politics, which casts Poles in the role of the primary victims of the war but is reluctant to speak out on the Shoah. The growing scholarly interest in the dark chapters in the history of Catholic-Jewish relations, which brings to light the Church’s institutional and symbolic responsibility for its attitude towards the persecuted Jewish community, has not translated directly into greater visibility of the issue in the mainstream media. However, the Church’s ceremonial indifference towards the memory of the Shoah is not resistant to changes in the historiography of the Shoah. The Church’s stance in the debate on the memory of the Shoah insufficiently recognises its position about the Jewish tragedy. On the other hand, it includes the actions undertaken by Father Wojciech Lemański and Bishop Rafał Markowski to commemorate the Jewish victims. The recognition of this cleavage aligns with sociological analyses of axiological divisions in Polish society.
p. 67-98
Keywords: Catholic Church and the Holocaust; public debate; pogroms; public memory; Shoah

Ujednolicanie dyskursów w państwie unaradawiającym: ugrupowania rządzące wobec ludności białoruskiej w II Rzeczypospolitej - Kurza, Katarzyna (Instytut Historii PAN, 2020)
The text is a contribution to the studies into the problems of adoption of nationalist orientation by a newly created state. It deals with the attitude of political groups wielding power in interwar Poland towards the indigenous Belarusian population. An analysis of public discourses conducted from the sociological perspective revealed the features characteristics of a nationalising state (in Rogers Brubaker’s understanding) in the attitudes of all camps of power and the unification of structures of the discourses they held.
p. 67-93
Summary in French and Russian.
Keywords: national state; nationalising state; nationalistic discourse; nationalism; nationalism - Poland - 1900-1945; Belarussians; Second Polish Republic

From Antemurale to Przedmurze, the History of the Term - Tazbir, Janusz (1927–2016) (2017)
p. 67-87
Keywords: Poland - civilization - 1500-1795; ideology - Poland - 1500-1795; political ideas - Poland - 1500-1800